Management of Acute Abdomen: Acute Appendicitis - Neupane, B. R.; Paudel, S. R.; Shrestha, A.; Bijukchhe, S. `M.; Bhattarai, A.; Subedi, P. (Journal of Gandaki Medical College-Nepal, 2019)
Background: Traditionally, appendectomy has been the treatment of choice for acute appendicitis but many times diagnosis can be difficult. Clinicians are looking through different ways to come to the correct diagnosis to decrease negative appendectomy. The aim of this study was to determine relation between clinical pattern, laboratory and ultrasonography findings with histopathological report of appendectomy specimen and to evaluate the Alvarado scoring regarding its usefulness in the early diagnosis in our set up.Methods: Prospective cross-sectional study was carried out in Gandaki Medical College Teaching Hospital and Fewa City Hospital from Jan 1, 2016 to Dec 31, 2018 on consecutively admitted patients with clinical diagnosis of acute appendicitis with study variables as demography, Alvarado score, radiological/laboratory investigations, surgical management, histopathology, and clinical outcome.Results: Among 1021 patients (48.8% men, 51.2% women), patients with Alvarado score offive and more (967, 88.8%) had abdominal USG and some (134) with score of 5-6 (13.12%) had CT scan. On the basis which 818patients (151 patients with score 5-6 and 667 with score 7 to 10) underwent emergency appendectomy; 705 (86.19%) by open and 113 (13.81%) by laparoscopic technique. Appendicitis was suggestive per-operatively in 76.2% of patients with Alvarado score of 5-6 and 97.4% of patients with the score of 7-10. Histo-pathologically diagnosis was correct in 752 (91.9%), 91.2% in open appendectomy and 96.5% in laparoscopic appendectomy cases. Only two patients had infective complication and no mortality.Conclusion: Alvarado scoring in patients presenting with acute abdominal pain is reliable predicting tool for acute appendicitis.